PENGARUH KOMPENSASI TERHADAP EMPLOYEE ENGANGEMENT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA RM PAUH PIAMAN KOTA PEKANBARU - Galuh, Pinkan Amarasesha; Andri, Seno (Jurnal Daya Saing, 2024)
This study aims to determine and analyse the effect of compensation (X) on employee engagement (Y) through job satisfaction (Z) at Pauh Piaman restaurant in Pekanbaru City. Research data obtained based on questionnaires distributed to employees at Pauh Piaman restaurant in Pekanbaru City. The method of sampling used total sampling technique of 38 respondents as the object of research. The research method used is quantitative method. Based on the results of the study, it was found that compensation had an effect on employee engagement on Pauh Piaman RM employees in Pekanbaru City, this was due to the value of the results of the Hypothesis Test based on the Path Coefficient by 0.286, then compensation had a significant positive effect on job satisfaction with a coefficient value of 0.756 and there was an effect of employee engagement on job satisfaction with a coefficient value of 0.511. Then the results of the Hypothesis Test based on Total Effects, the total effect value of 0.672 shows the greater influence of compensation on employee engagement, which reflects the overall contribution of compensation to employee engagement, including indirect effects through job satisfaction. Keywords: Compensation, employee engagement, job satisfaction